Primary grade 2 neuroendocrine tumor of the ileal mesentery: a case report - Shigemi Morishita; Shinichi Yoshida; Yasufumi Kamatani; Shinya Suzuhigashi; Masaki Kitou; Takuma Nasu (Surgical Case Reports, 2022)
Abstract Background The prevalence and incidence of neuroendocrine tumors (NETs) are increasing worldwide. Primary mesenteric NETs are extremely rare. Solid tumors that arise in the mesentery are typically metastatic. We present an extremely rare case of a primary grade 2 NET (NET G2) in the ileal mesentery. Case presentation A 54-year-old man was referred to our hospital for further examination of a previously diagnosed right mesenteric tumor. Mild tenderness was noted on the right side of the abdomen, but there were no palpable masses. Fluorodeoxyglucose-positron emission tomography (FDG-PET) revealed slight FDG uptake (maximum standardized uptake value, 2.0) in the right abdomen, and a benign or low-grade malignant tumor was suspected. We extracted the ileal mesenteric tumor with an ileal resection (90 cm). The cut surface of the 55 × 33 × 33 mm3 tumor was pale yellowish-white. Immunohistochemistry revealed diffuse staining for synaptophysin and chromogranin A, and focal staining for CD56. The Ki-67 index was 3%. The final pathological diagnosis was NET G2. The patient’s postoperative course was uneventful, and he developed no recurrence 1.5 years after surgery. Postoperative antitumor therapy was not performed for this patient because the histological diagnosis was NET G2, and it was determined that the tumor could be completely resected by surgery. Conclusions We report an extremely rare case of primary ileal mesenteric NET. Mesenteric tumors that show slight FDG uptake on FDG-PET examination should be considered well-differentiated NET.